THE INFLUENCE OF TAX MINIMIZATION, TUNNELING INCENTIVE, BONUS SCHEME AND DEBT COVENANT ON TRANSFER PRICING DECISION: THE INDONESIAN EVIDENCE - Qiansyah, Alifwan Arvinar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to analyse the influence of tax minimization, tunneling incentive, bonus scheme and debt covenant on transfer pricing decision of companies listed in Indonesia Stock Exchange (IDX). This study is uses 81 companies listed in IDX for the year of 2015 selected using a purposive sampling method. The logistic regression analysis is used as a data analysis method. The result shows that tax minimization does not influence a decision to do a transfer pricing, however tunneling incentive, bonus scheme, and debt covenant have an influenced on transfer pricing decisions.Â Keywords: Tax minimization, tunneling incentive, bonus scheme, transfer pricing